2006
DOI: 10.1002/art.22266
|View full text |Cite
|
Sign up to set email alerts
|

A novel autoantigen to differentiate limited cutaneous systemic sclerosis from diffuse cutaneous systemic sclerosis: The interferon‐inducible gene IFI16

Abstract: Objective. To investigate the presence and clinical significance of autoantibodies against the interferoninducible gene IFI16 in systemic sclerosis (SSc), systemic lupus erythematosus (SLE), and other autoimmune diseases.Methods. Immunohistochemical analysis was used to evaluate the expression of IFI16 in skin biopsy specimens obtained from patients with SSc and patients with SLE. Levels of antibodies against IFI16 in sera from 82 patients with SSc and 100 patients with SLE were determined by enzyme-linked imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 12 publications
(14 reference statements)
8
64
2
3
Order By: Relevance
“…The ubiquitination of STING is essential to facilitate dimerisation of the adaptor prior to the recruitment of TBK-1, thus marking TRIM56 as a positive facilitator of this pathway. IFI16 requires STING for its activity and is a well known autoantigen in systemic autoimmune disease [73]. The absolute requirement for STING in the production of IFN-β has come from the recent report of a loss-of-function variant in an American cohort that correlates with an approximate 90% loss of IFN-β inducibility in subjects homozygous for the mutation [74].…”
Section: Regulation Of Nucleic Acid Detection By Trimsmentioning
confidence: 99%
“…The ubiquitination of STING is essential to facilitate dimerisation of the adaptor prior to the recruitment of TBK-1, thus marking TRIM56 as a positive facilitator of this pathway. IFI16 requires STING for its activity and is a well known autoantigen in systemic autoimmune disease [73]. The absolute requirement for STING in the production of IFN-β has come from the recent report of a loss-of-function variant in an American cohort that correlates with an approximate 90% loss of IFN-β inducibility in subjects homozygous for the mutation [74].…”
Section: Regulation Of Nucleic Acid Detection By Trimsmentioning
confidence: 99%
“…The treatment of cells with short hairpin RNA, targeting IFI16 significantly inhibited ICAM-1 induction by IFN-g demonstrating that IFI16 is required for proinflammatory gene stimulation by this cytokine. Moreover, functional analysis of the ICAM-1 promoter demonstrated that NF-kB, one of the main transcription factors activated during inflammation, is the main mediator of IFI16-driven ICAM-1 induction by IFN-g. Additionally, anti-IFI16 autoAb are present at much greater levels in patients with autoimmune diseases, such as cutaneous systemic sclerosis, systemic lupus erythematosus and Sjogren's syndrome, compared with normal controls [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Riemekasten et al [25] beschrieben stimulatorische Antikörper gegen Typ-I-Rezeptoren von Angiotensin II und gegen Typ-A-Rezeptoren von Endothelin I, die bei SSc, aber auch bei anderen Kollagenosen und rheumatoider Arthritis -allerdings in niedrigeren Titern -vorkommen. Die diagnostische Relevanz dieser stimulatorischen Autoantikörper, zu denen auch Antikörper gegen das Interferon-induzierbare Protein IFI16 zählen [21], bedarf weiterer Untersuchungen.…”
Section: Stimulatorische Autoantikörper Bei Systemischer Sklerodermieunclassified